The Moderating Role of Maternal Education and Employment on Child Health in Pakistan - Muhammad Farhan Asif; Shafaqat Ali; Majid Ali; Ghulam Abid; Zohra S. Lassi (MDPI AG, 2022)
Background: Pakistan has challenges in fulfilling its universal responsibilities of providing better health facilities to everyone. The Sustainable Development Goals (SDGs) aim to reduce maternal and infant mortality rates. Despite declines in mother and child death, the total mortality ratio has marginally increased. However, neonatal death has not decreased significantly. Family planning is important for controlling population growth and improving child as well as maternal health. Pakistan's government has unceasingly tried to enhance the provision of contraceptive facilities, but still, an unmet need for family planning (UMNFP) exists in our country. Women are said to have UMNFP if they want to limit or space childbearing, but they are not using contraception methods for any reason. The study aimed to explore the effect of the UMNFP and to investigate the moderating role of a mother's education and employment status on a child's health. Methods: We analyzed the data of 2,244 women in this study. To investigate the study objectives, we utilized the secondary dataset of the Pakistan Demographic and Health Survey (PDHS) 2017-18 (publicly available on the website of the National Institute of Population Studies) and applied binary logistic regression using SPSS 24. Results: Results suggest a positive effect of a woman's age (25 to 39 years), maternal education (higher), father's education (higher), family's wealth status (richest), mass media exposure, and adequate birth spacing (at least for 33 months) on a child's health. On the other hand, there is an indirect association between maternal employment, unmet need for family planning, and a child's health. The moderating role of maternal education and employment on the relationship between household wealth status and a child's health is positive. Conclusions: We conclude that the strong predictors of child health are UMNFP, maternal education, and employment. The link between the met need for family planning and the child's health is positive. The moderating effect of maternal education and household wealth status on a child's health is progressive. Similarly, the interaction effect of a mother's employment and household wealth status on a child's health is positive. Finally, we concluded that the link between the health of the child and household wealth status is much more diverse and positive when the mother is highly educated and currently employed.